Pembiasaan Keagamaan melalui Kelas Mengaji dalam Membentuk Karakter Religius Siswa di SMP Hasan Munadi Beji Pasuruan - Wulandari, Fitri; Munir, Miftakhul; M. Ma’ruf (Universitas Islam Lamongan, 2025)
This study describes the implementation and impact of religious habituation through Quranic recitation classes in shaping the religious character of students at Hasan Munadi Beji Pasuruan Middle School. A qualitative case study approach was used, using observation, in-depth interviews, and documentation techniques. The results indicate that the Quranic recitation class program was implemented in a planned manner through planning, implementation, and evaluation stages. This program had a positive impact on improving the ability to read the Quran and developing students' religious character, such as diligent worship, noble character, discipline, tolerance, and understanding of Islamic teachings.